Exploiting Minimalistic Backbone Engineered γ‐Phenylalanine for the Formation of Supramolecular Co‐Polymer. Issue 19 (12th August 2022) - Misra, Rajkumar; Tang, Yiming; Chen, Yujie; Chakraborty, Priyadarshi; Netti, Francesca; Vijayakanth, Thangavel; Shimon, Linda J. W.; Wei, Guanghong; Adler‐Abramovich, Lihi
Abstract: Ordered supramolecular hydrogels assembled by modified aromatic amino acids often exhibit low mechanical rigidity. Aiming to stabilize the hydrogel and understand the impact of conformational freedom and hydrophobicity on the self‐assembly process, two building blocks based on 9‐fluorenyl‐methoxycarbonyl‐phenylalanine (Fmoc‐Phe) gelator which contain two extra methylene units in the backbone, generating Fmoc‐ γ Phe and Fmoc‐(3‐hydroxy)‐ γ Phe are designed. Fmoc‐ γ Phe spontaneously assembled in aqueous media forming a hydrogel with exceptional mechanical and thermal stability. Moreover, Fmoc‐(3‐hydroxy)‐ γ Phe, with an extra backbone hydroxyl group decreasing its hydrophobicity while maintaining some molecular flexibility, self‐assembled into a transient fibrillar hydrogel, that later formed microcrystalline aggregates through a phase transition. Molecular dynamics simulations and single crystal X‐ray analyses reveal the mechanism underlying the two residues' distinct self‐assembly behaviors. Finally, Fmoc‐ γ Phe and Fmoc‐(3‐OH)‐ γ Phe co‐assembly to form a supramolecular hydrogel with notable mechanical properties are demonstrated. It has been believed that the understanding of the structure‐assembly relationship will enable the design of new functional amino acid‐based hydrogels. Abstract : Ordered supramolecular hydrogels assembled by modified aromatic amino acids often exhibit low mechanical rigidity. Aiming to stabilize the hydrogel and understand the impact of conformational freedom and hydrophobicity on the self‐assembly process, two building blocks containing the minimal Fmoc‐ γ Phenylalanine were designed. Spontaneous assembly in aqueous media allowed the formation of hydrogels with exceptional mechanical and thermal stability.